2017
DOI: 10.29312/remexca.v7i1.368
|View full text |Cite
|
Sign up to set email alerts
|

Aislamiento y caracterización de celulosas obtenidas de fibras de Agave salmiana aplicando dos métodos de extracción ácido-alcali

Abstract: ResumenPara aprovechar las pencas de agaves (A. salmiana) una vez que se retiran de la piña de la planta, se obtuvieron fibras. Las hojas fueron tratadas con hidrólisis ácida (HCl) e hidrólisis alcalina (NaOH), usando presión de 1.1 kg/cm 2 (FACT ácido-álcali con presión), a 121 °C por 4 h y otro tratamiento a presión atmosférica con reflujo (FACT ácido-álcali sin presión). Se determinó el porcentaje de celulosa y lignina, así como los cambios fisicoquímicos por medio de calorimetría diferencial de barrido (DS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
(34 reference statements)
3
1
0
1
Order By: Relevance
“…The decrease indicated that there was cellulose degradation. These results also agree with the chemical characterization results [ 46 , 47 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The decrease indicated that there was cellulose degradation. These results also agree with the chemical characterization results [ 46 , 47 ].…”
Section: Resultssupporting
confidence: 92%
“…A decrease in absorbance at this peak was observed in all the pre-treatments, with the enzymatic pre-treatment demonstrating the most pronounced decrease, followed by the acid-enzymatic pre-treatment, consistent with research by Ref. [ 46 ]. The decrease indicated that there was cellulose degradation.…”
Section: Resultssupporting
confidence: 91%
“…It is believed that the crystallinity index in micro cellulose increases due to the elimination of the amorphous regions of cellulose, in which hydrolysis drives the breakdown of glycosidic bonds, releasing individual crystals [56] . The crystallinity of mango micro cellulose reported in this study is similar to that reported by Bolio-López et al [57] in banana peel micro cellulose (72% crystallinity) but greater than that obtained by Naranjo et al [47] in agave fibre (50.07%). The greater the crystallinity of a fibre, the better the thermal stability and properties it can provide in a polyblend to obtain biodegradable materials [58] .…”
Section: Crystallinitysupporting
confidence: 90%
“…A narrow absorption band in the region between 1170 and 920 cm -1 ascribed to the polysaccharide bands, shows the stretching vibrations of C -O, C -C and C -OH bonds which are in cellulose, lignin and hemicellulose [46,47] . A strong signal was present in the treated fibre (MC).…”
Section: Ftir Analysismentioning
confidence: 99%
“…De acuerdo con algunos investigadores, la hidrólisis ácida con H 2 SO 4 o HCl en concentraciones menores al 5 % de distintas fuentes vegetales, proveen una adecuada hidrólisis de hemicelulosa con poca descomposición de azúcares reductores (Aguilar et al, 2008;Monsalve et al, 2006;Naranjo et al, 2016); sin embargo, la cristalinidad es una barrera física que dificulta la accesibilidad a los enlaces 1,4 glucosídicos que unen las cadenas de glucosa en la celulosa, razón por la cual concentraciones del 10 al 16 % (Domínguez-Domínguez et al, 2012;Reis et al, 2007) han dado resultados prometedores en la hidrólisis de bagazo de caña de azúcar y bagazo de malta (Mussatto et al, 2006) para el aprovechamiento de etanol. Por otra parte, el tratamiento de hidrólisis con H 3 PO 4 favorece la disolución de lignina con poco efecto sobre la celulosa (Domínguez-Dominguez et al, 2012), lo que explicaría la baja proporción de azúcares reductores obtenidos con la hidrólisis a base de H 3 PO 4 con respecto al H 2 SO 4 y NaOH en esta investigación.…”
Section: Rendimiento De La Hidrólisisunclassified